Phenomenology in Gerontology: From Philosophy to Method - Hamedanchi, Arya; Zanjari, Nasibeh; Khankeh, Hamid R.; Momtaz, Yadollah Abolfathi (Current Psychiatry Research and Reviews, 2021)
Background: Ageing is a complex phenomenon, which can vastly influence different dimensions of life. One of the main concerns in gerontology is to understand how older adults experience ageing and its associated conditions. The aim of this study was to determine the role of phenomenology as a qualitative method in gerontology research. Methods: In this review study, we summarized the key concepts in gerontology, reviewed the philosophy and methodology of phenomenology, presented both descriptive and interpretive phenomenological methods, and highlighted the areas which can be explored in ageing by phenomenology. We also presented some examples for studying the lived experiences of older adults using phenomenological methods. Results: People experience noticeable changes in their body, emotions and social relations as they grow old. The biopsychosocial aspects of ageing are discussed in gerontology as a growing interdisciplinary science. Phenomenology allows the researchers to obtain a deep understanding of older adults lived experiences and it can connect the investigators of this discipline to the inner world of ageing adults. Conclusion: Based on the findings, it can be concluded that ageing is an important experience in life, and phenomenological reflection on the lived experiences of older adults can play a crucial role in increasing our knowledge about ageing.
Keywords: phenomenology